Investigation of cellular responses upon interaction with silver nanoparticles - Subbiah, Ramesh; Jeon, Seong Beom; Park, Kwideok; Ahn, Sang Jung; Yun, Kyusik (DOVE MEDICAL PRESS LTD, 2015)
In order for nanoparticles (NPs) to be applied in the biomedical field, a thorough investigation of their interactions with biological systems is required. Although this is a growing area of research, there is a paucity of comprehensive data in cell-based studies. To address this, we analyzed the physicomechanical responses of human alveolar epithelial cells (A549), mouse fibroblasts (NIH3T3), and human bone marrow stromal cells (HS-5), following their interaction with silver nanoparticles (AgNPs). When compared with kanamycin, AgNPs exhibited moderate antibacterial activity. Cell viability ranged from <80% at a high AgNPs dose (40 mu g/mL) to.95% at a low dose (10 mu g/mL). We also used atomic force microscopy-coupled force spectroscopy to evaluate the biophysical and biomechanical properties of cells. This revealed that AgNPs treatment increased the surface roughness (P < 0.001) and stiffness (P<0.001) of cells. Certain cellular changes are likely due to interaction of the AgNPs with the cell surface. The degree to which cellular morphology was altered directly proportional to the level of AgNP-induced cytotoxicity. Together, these data suggest that atomic force microscopy can be used as a potential tool to develop a biomechanics-based biomarker for the evaluation of NP-dependent cytotoxicity and cytopathology.
Keywords: ATOMIC-FORCE MICROSCOPY; DIFFERENTIATION; CELLS